A Survey of Intravenous Remifentanil Use for Labor Analgesia at Academic Medical Centers in the United States. (April 2017) - Aaronson, Jaime; Abramovitz, Sharon; Smiley, Richard; Tangel, Virginia; Landau, Ruth
Abstract : Remifentanil is most commonly offered when neuraxial labor analgesia is contraindicated. There is no consensus regarding the optimal administration, dosing strategy, or requirements for maternal monitoring, which may pose a patient safety issue. This exploratory survey evaluated the current practices regarding remifentanil use for labor analgesia at academic centers in the United States. Of 126 obstetric anesthesia directors surveyed, 84 (67%) responded. In 2014 to 2015, an estimated 36% (95% confidence interval: 25.7–46.3) of centers used remifentanil, most of which did so less than 5 times. Some serious maternal and neonatal respiratory complications occurred, emphasizing that clinical protocols and adequate monitoring are key to ensure maternal and neonatal safety. Abstract : Supplemental Digital Content is available in the text.Published ahead of print September 20, 2016.